Computational fluid flow and heat transfer - Muralidhar, K.; Sundarajan, T. (IIT Kanpur series of advanced texts., 2003)
A technique that combines the benefits of finite differences and finite elements. It is applicable to three dimensional unsteady flows in complex geometrie. It uses structured collocated grids, the grids themselves can be orthogonal or non-orthogonal.